Identificação e manejo de ressonâncias em parques eólicos: aplicação dos conversores TUPF - Camila Elias Almeida (2019)
The growing expansion in the use of distributed sources for the generation of electric-ity brought the increased use of power static converters connected directly to the electrical distri-bution network. While the individual harmonic emission of each converter may be within the lim-its recommended by national and international standards, the installation of several equipment of this type in a single point of connection to the electrical system, especially if associated with a weak grid, may cause excessive distortion levels, which may exceed regulation limits, cause mal-function of control systems and excite resonances, which may not be mitigated by damping strat-egies provided by the manufacturers. Given this scenario is established interest in developing static power converters em-ploying modulation techniques and other strategies that, instead of reducing the harmonic current components normally injected by the equipment, seek to eliminate them or not allow their occur-rence in the power generation process, that is, equipment that essentially behaves as sinusoidal current sources, preferably without the use of passive filters. The typical filter capacitances, de-signed to limit the reactive power drained from the network, have the undesired effect of reducing the frequencies of occurrence of series resonances. The goal of this work is to establish the true unit power factor converter as an advan-tageous topology of power conditioning system for wind power generation, capable of meeting power quality requirements and simultaneously modifying the resonance characteristics in farms in a favorable way.